Effects of lack of microRNA-34 on the neural circuitry underlying the stress response and anxiety. (August 2016) - Andolina, Diego; Di Segni, Matteo; Bisicchia, Elisa; D'Alessandro, Francesca; Cestari, Vincenzo; Ventura, Andrea; Concepcion, Carla; Puglisi-Allegra, Stefano; Ventura, Rossella
Abstract: Stress-related psychiatric disorders, including anxiety, are complex diseases that have genetic, and environmental causes. Stressful experiences increase the release of prefrontal amygdala neurotransmitters, a response that is relevant to cognitive, emotional, and behavioral coping. Moreover, exposure to stress elicits anxiety-like behavior and dendritic remodeling in the amygdala. Members of the miR-34 family have been suggested to regulate synaptic plasticity and neurotransmission processes, which mediate stress-related disorders. Using mice that harbored targeted deletions of all 3 members of the miR-34-family (miR-34-TKO), we evaluated acute stress-induced basolateral amygdala (BLA)-GABAergic and medial prefrontal cortex (mpFC) aminergic outflow by intracerebral in vivo microdialysis. Moreover, we also examined fear conditioning/extinction, stress-induced anxiety, and dendritic remodeling in the BLA of stress-exposed TKO mice. We found that TKO mice showed resilience to stress-induced anxiety and facilitation in fear extinction. Accordingly, no significant increase was evident in aminergic prefrontal or amygdala GABA release, and no significant acute stress-induced amygdalar dendritic remodeling was observed in TKO mice. Differential GRM7, 5-HT2C, and CRFR1 mRNA expression was noted in the mpFC and BLA between TKO and WT mice. Our data demonstrate that the miR-34 has a critical function in regulating the behavioral and neurochemical response to acute stress and in inducing stress-related amygdala neuroplasticity. Highlights: Mice lacking miR-34 no show neurochemical, behavioral and morphological response to stress. Potential role of miR-34 in modulating prefrontal-amygdala response to stress. Mice model of resilience to stress effects. Potential role of miR-34 in modulating the stress-induced anxiety.